2023
DOI: 10.1002/aenm.202204192
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Interfacial Termination via Dipole Interlayer for High‐Efficiency Perovskite Solar Cells

Abstract: The ionic nature of the organic‐inorganic hybrid perovskite material is prone to react with different functional groups. Here, a series of polar molecules with permanent dipole moments are designed to modify the perovskite surface termination. It is observed that proper interfacial design can significantly reduce trap state density for effective charge transfer. The energy level of the substrate can be adjusted by the magnitude and direction of the dipole moment. As a result, a high 24.54% photo‐electric conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…[ 88,89 ] Recently, numerous works demonstrated the feasibility and high effectiveness of surface dipole on perovskite layer with multiple functionalities such as tuning surface energetics, reducing surface defects, and enhancing stability. [ 90–93 ]…”
Section: Tuning Perovskite Surface Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 88,89 ] Recently, numerous works demonstrated the feasibility and high effectiveness of surface dipole on perovskite layer with multiple functionalities such as tuning surface energetics, reducing surface defects, and enhancing stability. [ 90–93 ]…”
Section: Tuning Perovskite Surface Energeticsmentioning
confidence: 99%
“…perovskite layer with multiple functionalities such as tuning surface energetics, reducing surface defects, and enhancing stability. [90][91][92][93] The work function of perovskite surface can be finely tuned in terms of both magnitude and direction by the dictation of surface dipole. For example, Canil et al reported a controllable shift over several hundreds of meV for perovskite work function by managing surface dipole coverage.…”
Section: Surface Dipole Formationmentioning
confidence: 99%
“…24 Liu et al demonstrated that the dipole moment of additives has a positive effect in reducing trap state density. 25 Pang et al confirmed the importance of molecular dipoles in amplifying the passivation effect of additive molecules. Moreover, Yang et al showed that the ligand intrinsic dipole moment and a charge-density displacement by ligand–surface interactions and bond formation can affect the work function change.…”
Section: Introductionmentioning
confidence: 97%
“…The methods to improve the efficiency of PSC devices include controlling perovskite crystal growth, interface modification, and innovative optimization of charge transport layers. The traditional HTM used in p – i – n devices is PTAA. However, PTAA as a polymer, its complex synthesis process and purification process, leading to the expensive price, and the poor synthesis repeatability also seriously restrict the device commercialization. , It is reported that the organic small-molecule HTMs can not only transport holes but can also form self-assembled monolayers on ITO or passivate the perovskites to significantly reduce nonradiative recombination, generating a PCE of the inverted device as high as 25.4%. Therefore, organic small-molecule HTMs are ideal candidates due to their simple synthesis, clear structure, and ability to further interact with ITO or perovskite through specific element groups, which can passivate the interface contact and reduce radiative recombination. However, organic small-molecule HTMs that can interact with both ITO and perovskite in inverted PSCs are rarely reported.…”
Section: Introductionmentioning
confidence: 99%